Investigation of Potential Molecular Targets of Zanthoxylum acanthopodium in Ovarian Cancer Using Network Pharmacology Assessments - Wijaya, Johanna Fransiska; Chiuman, Linda; Syahputra, Hariyadi Dharmawan; Kaban, Vera Estefania; Razoki, Razoki; Ginting, Chrismis Novalinda; Iksen, Iksen (Pandawa Institute, 2025)
Ovarian cancer is a serious disease that affects the ovaries, and its early detection is challenging due to vague symptoms often dismissed as minor ailments. Currently, natural sources have gained attention for their potential role in anticancer treatment. This study aimed to utilize network pharmacology to explore the potential targets and mechanisms of Zanthoxylum acanthopodium in the treatment of ovarian cancer. This study utilized the KNApSAcK and Swiss Target Prediction to identify active compounds and target genes. Additionally, ovarian cancer-specific target genes were sourced from the GEO database. To identify possible key target genes, the network interaction between protein-protein using the STRING database and visualized them in Cytoscape. Subsequent analysis using Gene Ontology (GO) and the Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways enabled us to focus on primary therapeutic targets. Our investigation into Zanthoxylum acanthopodium revealed 10 active compounds that pass Lipinski rule of five and oral bioavailability with acceptable pharmacokinetic profiles, 88 therapeutic targets, and identified 5 hub genes: SRC, CCNB2, MMP9, PTGS2, and PTPRC, which are strongly associated with ovarian cancer progression. Pathway enrichment analysis highlighted several pathways significantly related to the pathogenesis of ovarian cancer. This study elucidates the therapeutic potential and mechanisms of action of Z. acanthopodium as a promising candidate for ovarian cancer treatment. However, further research, including both in vitro and in vivo studies, is necessary to understand its molecular mechanisms comprehensively.